Incidence and care of environmental dermatoses in the high-altitude region of Ladakh, India - G K Singh; Manas Chatterjee; R S Grewal; Rajesh Verma (Wolters Kluwer Medknow Publications, 2013)
Background : Low humidity, high-velocity wind, excessive ultraviolet (UV) exposure, and extreme cold temperature are the main causes of various types of environmental dermatoses in high altitudes. Materials and Methods: A retrospective study was carried out in patients visiting the lone dermatology department in Ladakh between July 2009 and June 2010. The aim was to identify the common environmental dermatoses in high altitudes so that they can be treated easily or prevented. The patients were divided into three demographic groups, namely, lowlanders, Ladakhis (native highlanders), and tourists. Data was analyzed in a tabulated fashion. Results: A total of 1,567 patients with skin ailments were seen, of whom 965 were lowlanders, 512 native Ladakhis, and 90 were tourists. The skin disorders due to UV rays, dry skin, and papular urticaria were common among all groups. The frequency of melasma ( n = 42; 49.4%), chronic actinic dermatitis (CAD) ( n = 18; 81.81% of total CAD cases), and actinic cheilitis ( n = 3; 100%) was much higher among the native Ladakhis. The frequency of cold-related injuries was much lesser among Ladakhis ( n = 1; 1.19%) than lowlanders ( n = 70; 83.33%) and tourists ( n = 13; 15.47%) ( P < 0.05). Conclusion: Dryness of skin, tanning, acute or chronic sunburn, polymorphic light reaction, CAD, insect bite reactions, chilblain, and frostbite are common environmental dermatoses of high altitudes. Avoidance of frequent application of soap, application of adequate and suitable emollient, use of effective sunscreen, and wearing of protective clothing are important guidelines for skin care in this region.